Carbamazepine-ibuprofen co-crystal screening using non-stoichiometric method - Nurul Aini, Rosli (2014)
Co-crystals is a facilitating technology that is used in new or existing drug delivery systems by majority of pharmaceutical companies in formulation of drug development. However the challenging aspects in development of drug molecules are correlated with their slow dissolution in biological fluids and thus insufficient and inconsistent systemic exposure, and consequent sub-optimal clinical effectiveness. The traditional approaches to deal with the issues of poor aqueous solubility often fail to create a viable solid form which is insufficient to provide enough enhancement of bioavailability. And so, there is enormous potential to explore co-crystal design of marketed APIs among each other to enhance the solubility and bioavailability of the product. This paper presents the co-crystal screening approach through the study of carbamazepine (CBZ) and ibuprofen (IBU). The screening was conducted using non-stoichiometric methods (solid addition of CBZ to saturated solution of IBU). In the experiment, CBZ-IBU co-crystal was prepared in various solvents and left to equilibrate in three conditions; stagnant, manually agitated and shaken in three days to produce the co-crystal. Physical characterization of the solid co-crystal is being characterized by using optical microscopy for it morphology as well by using differential scanning calorimetry (DSC) to determine the thermal properties. The only co-crystal of CBZ-IBU success to form using the non-stoichiometric approach is in formic acid solvent whereas for the others, they behaving more likely to be CBZ in different forms. Overall, DSC analysis shows that either CBZ or IBU occured due to the peak which corresponded to their melting point. From this study, it can be concluded that co-crystal formation between CBZ-IBU using non-stoichiometric method only successful in formic acid